STRATEGIC PLANNING: SHAPING OR EMERGING FROM ORGANISATIONS - Sugiono, Sugiono (JURNAL AL-TANZIM, 2018)
This paper focuses on the literature exploration of perspectives of strategic planning in terms of whether it shapes or emerges from organisations. The paper argues that to make judgment on an organisational performance as a result of planned strategies or emergent ones is not easy.  Essentially, strategic planning aims to direct the performance of an organisation in order to attain its desired and planned goals. However, the organisation environment often changes rapidly, and hence it cannot be predicted and controlled. Such a circumstance potentially provides a particular impact on the organisation performance. In this situation, the strategic planning is inevitably shaped by the emergent strategy, which means that the realised strategy is the logical consequence of interactions between planned strategies and emergent ones. It has been suggested that a good strategic planning is to be flexible and open to a process of strategic learning, by which creativity and personnel’s commitment could be enhanced.